Long term outcomes following anti-VEGF therapy for diabetic macular edema. (3rd September 2022) - Maatouk, Christopher M.; Sastry, Resya; Singh, Rishi P.
ABSTRACT: Introduction: Anti-VEGF agents have been demonstrated to be more effective than sham or laser in treating center-involving diabetic macular edema (DME) in short-term pivotal trials. The literature regarding long-term outcomes (5 years or more) of anti-VEGF treatments in DME is limited. Areas covered: A literature search was conducted using the PubMed and Cochrane Library databases. Key words included 'diabetic macular edema, ' 'diabetic retinopathy, ' 'vascular endothelial growth factor, ' 'anti-VEGF, ' 'long*, ' and 'five-year.' 21 articles were included in the final review that examined the 5-year visual and anatomic outcomes of anti-VEGF treatments in DME. Combined analysis of the mean 5-year change in visual acuity and central retinal thickness was conducted. Expert opinion: Anti-VEGF agents provide significant vision and anatomic improvements to patients with DME through at least 5 years of treatment. Given their minimal adverse effect profile, superior impact on visual and anatomic outcomes, and likely cost benefit, anti-VEGF agents should be initiated as early as possible in individuals with clinically significant DME causing vision loss. Further work is required to identify early indicators of poor treatment response and to develop longer-acting anti-VEGF treatments.